Implementation of a Cost-Effective, Accurate Photoacoustic Imaging System Based on High-Power LED Illumination and FPGA-Based Circuitry - AHANGAR DARBAND, Maryam; NAJAFIAGHDAM, Esmaeil (Archives of Acoustics, 2025)
Imaging based on the photoacoustic (PA) phenomenon is a type of hybrid imaging approach that combines the advantages of pure optical and pure acoustic imaging, achieving good results. This method, which offers high resolution, suitable contrast, and non-ionizing radiation, is valuable for the early detection of various types of cancer. Recently, multiple studies have focused on improving different components of this imaging system. In this presentation, we implemented a simplest form of a PA imaging system for detecting blood vessels, given that angiogenesis is recognized as a common symptom of many cancers. For the first time, we implemented a high-power light-emitting diode (LED), to replace bulky and expensive lasers, and integrated circuit technologies such as field-programmable gate arrays (FPGAs) for a simple LED driver circuit and data acquisition (DAQ). Using an FPGA block, we successfully generated a 200-ns square pulse wave with a repetition frequency of 25 kHz, whose amplified form can drive a high-power LED at 1050 nm for appropriately stimulating the sample. By using ultrasonic sensors with a central frequency of 1 MHz and a DAQ system with 16-bit accuracy, along with a suitable algorithm for image reconstruction, we successfully detected blood vessels in a breast tissue mimic. With the use of the FPGA-based block, the image reconstruction algorithm was accelerated. Finally, the simultaneous and first-time use of LED and FPGA-based circuit technology for driving the LED, output information processing and image reconstruction were performed in PA imaging.